SOCIETY COMMUNICATION ON THE PERFORMANCE OF STEAM POWER PLANT (PLTU) - Febriany Febriany; Uljanatunnisa Uljanatunnisa (Metakom, 2019)
The waste produced by Steam Power Plant (PLTU) in Taweli Sub-district has negative impact on public health because the disposal process is not performed properly, causing Society communication such as demonstration. This research aims to describe and analyze the communication behavior of people in Taweli Sub-district in relation to the performance of Steam Power Plant (PLTU). This study used a qualitative approach with a case study method. The research results are divided into three indicators, namely (a) The initial information obtained by the Taweli Subdistrict Society related to the construction and performance of the Steam Power Plant (PLTU) was positively welcomed (b) Information on waste disposal by the Steam Power Plant (PLTU) was made into the society as a negative, and (c) The response given by the Taweli Sub-district Society and the people of Palu City was by conducting a demonstration.